2023
DOI: 10.1002/solr.202201129
|View full text |Cite
|
Sign up to set email alerts
|

Thermal‐Induced Cerium‐Doped Perovskite Solar Cells with a Fill Factor Exceeding 81%

Abstract: Hybrid organic–inorganic perovskites have attracted significant attention due to their remarkable optoelectronic properties and the feasibility of cost‐effective, high‐throughput manufacturing of perovskite solar cells (PSCs). The present p–i–n PSCs have poor film‐forming ability on poly[bis(4‐phenyl)(2,4,6‐trimethylphenyl)‐amine] (PTAA) film, resulting in a great number of defects within perovskite. Herein, the cerium ion (Ce3+) into the PTAA layer is successfully incorporated, which is thermal‐induced transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Thus, the passivation of the thin films by M1 and M2 has no effect on the absorption limit of the MAPb(I 0.97 Br 0.03 ) 3 thin film, resulting in a uniform band gap. The uniform band gap can be determined using the following formula: E g = 1240 λ normalg where λ g is the band edge wavelength (775 nm). The calculated E g = 1.6 eV, and the Fermi energy level ( E Fermi ), highest occupied molecular orbital energy level ( E HOMO ), and lowest unoccupied molecular orbital energy level ( E LUMO ) can be determined using the following formulas: E Fermi = W F + E cutoff , 0.25em E HOMO = W F + E onset , 0.25em E LUMO = E HOMO + E g where E onset is the onset potential.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the passivation of the thin films by M1 and M2 has no effect on the absorption limit of the MAPb(I 0.97 Br 0.03 ) 3 thin film, resulting in a uniform band gap. The uniform band gap can be determined using the following formula: E g = 1240 λ normalg where λ g is the band edge wavelength (775 nm). The calculated E g = 1.6 eV, and the Fermi energy level ( E Fermi ), highest occupied molecular orbital energy level ( E HOMO ), and lowest unoccupied molecular orbital energy level ( E LUMO ) can be determined using the following formulas: E Fermi = W F + E cutoff , 0.25em E HOMO = W F + E onset , 0.25em E LUMO = E HOMO + E g where E onset is the onset potential.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, studies have demonstrated that thermal-induced Ce 3+/4+ -doped MAPbI 2.91 Br 0.09 thin films exhibit improved film morphology and suppresses nonradiative recombination. 37 Encapsulation of a PMMA top layer has been found to enhance the ASE properties of CsPb(Br 0.5 Cl 0.5 ) 3 . Reportedly, the physical properties of halide perovskites can be modified by replacing the cations or halide components (I, Br, and Cl) to form mixed halide perovskites (MHPs).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous strategies have been developed to improve the optoelectronic efficiency and operational stability of halide perovskites. For instance, studies have demonstrated that thermal-induced Ce 3+/4+ -doped MAPbI 2.91 Br 0.09 thin films exhibit improved film morphology and suppresses nonradiative recombination . Encapsulation of a PMMA top layer has been found to enhance the ASE properties of CsPb­(Br 0.5 Cl 0.5 ) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Metal halide perovskite solar cells (PSCs) have emerged as a new photovoltaic technology, garnering considerable attention in both academic and industrial sectors because of their superior optoelectronic properties and simple preparation technologies. [1][2][3][4][5][6] They are represented by the general formula ABX 3 , where A represents a monovalent cation (e.g., CH 3 NH 3 + (MA + ), NH 2 CHvNH 2 + (FA + ), or Cs + ), B denotes a metal cation (e.g., Pb 2+ and Sn 2+ ), and X corresponds to a halogen anion (e.g., I − , Br − , and Cl − ). [7][8][9][10] The ease of compositional tunability in perovskites contributes to their tunable bandgap and optoelectronic properties, making them suitable for use in various applications.…”
Section: Introductionmentioning
confidence: 99%
“…Metal halide perovskite solar cells (PSCs) have emerged as a new photovoltaic technology, garnering considerable attention in both academic and industrial sectors because of their superior optoelectronic properties and simple preparation technologies. 1–6 They are represented by the general formula ABX 3 , where A represents a monovalent cation ( e.g. , CH 3 NH 3 + (MA + ), NH 2 CHNH 2 + (FA + ), or Cs + ), B denotes a metal cation ( e.g.…”
Section: Introductionmentioning
confidence: 99%